ValiErlang: A Structural Testing Tool for Erlang Programs - Oliveira, Alexandre P.; Souza, Paulo S. L.; Souza, Simone R. S. (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2016: Anais do I Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2016)
Validation, verification and testing are essential and contribute to improve the quality of programs, independent of the programming paradigm. In the context of functional language, aspects such as immutable data, higher-order functions, lazy evaluation and pattern matching impose restrictions to the structural testing software activity, which require special attention from testers. This paper presents a tool, called ValiErlang, which implements specific testing criteria for sequential and parallel Erlang programs, the latter using the message-passing paradigm. The ValiErlang is split into five modules and all of them have been detailed. Based on pre-defined criteria, the tool evaluates the obtained coverage by criteria, thus, the tester can evaluate the quality of the program being tested.